The Influence of the 2022 World Cup On Engineering Student Enthusiasm Learning in Physic Class - Indri Dayana (Universitas Syiah Kuala, 2023)
The 2022 world cup is one of the much-awaited world events, especially for men. Even though there are some engineering students who are female, they are still dominated by men. The program to watch the world cup ball, whose broadcast time is more often at night or early in the morning, makes engineering students watching drowsy and unfit due to lack of sleep. This has an impact on the enthusiasm for learning in class which makes engineering students' motivation to study decrease.Data analysis technique used is by regression analysis. From the results of the analysis it was found that Freghitung= 4.282 and Freg-table = 4.130 (Freg-count Freg-table), sample of 36 engineering students in physic class was taken so the conclusion of this study is that there is a very large influence decreased enthusiasm for learning during the world cup for engineering students at the University of Medan Area.